Public Officials, Social Media, and Criminal Defamation: Rethinking Responsibility under Indonesia’s ITE Law - Hartanto, Hartanto (UIN Sunan Kalijaga Yogyakarta, 2025)
The expanding use of social media by public officials has transformed governmental communication into a real-time, direct, and wide-reaching practice, while simultaneously generating new legal tensions concerning criminal defamation and responsibility for reputational harm in digital environments. This paper seeks to propose how a balance between freedom of expression and the public official’s function of disseminating information through media and the constitutional protection of individual honor can be formulated within the framework of criminal liability for defamation on social media under the ITE Law. This study employs a normative legal research method using statutory and conceptual approaches, supplemented by a case approach through the controversy of DN versus AR as a public official in Surabaya as an illustrative instance of the application of Article 27A juncto Article 45(4) of the ITE Law. Primary and secondary legal materials were analyzed prescriptively to examine the role of social media as a medium of communication, the element of intent (dolus), and the positional consequences of public officials in criminal liability. The findings show that the ITE Law does not merely function as a repressive instrument against citizens, but also as an institutional control mechanism that imposes a duty of care on public officials when communicating through social media. The criminal defamation provisions under Article 27A in conjunction with Article 45(4) ITE Law establish constitutional and penal boundaries that restrict public officials’ freedom of expression, requiring accuracy, verification, and proportionality to prevent reputational harm.